Factors influencing referrals for ultrasound-diagnosed complications during prenatal care in five low and middle income countries - Holly L. Franklin; Waseem Mirza; David L. Swanson; Jamie E. Newman; Robert L. Goldenberg; David Muyodi; Lester Figueroa; Robert O. Nathan; Jonathan O. Swanson; Nicole Goldsmith; Nancy Kanaiza; Farnaz Naqvi; et al. (BMC, 2018)
Abstract Background Ultrasound during antenatal care (ANC) is proposed as a strategy for increasing hospital deliveries for complicated pregnancies and improving maternal, fetal, and neonatal outcomes. The First Look study was a cluster-randomized trial conducted in the Democratic Republic of Congo, Guatemala, Kenya, Pakistan and Zambia to evaluate the impact of ANC-ultrasound on these outcomes. An additional survey was conducted to identify factors influencing women with complicated pregnancies to attend referrals for additional care. Methods Women who received referral due to ANC ultrasound findings participated in structured interviews to characterize their experiences. Cochran-Mantel-Haenszel statistics were used to examine differences between women who attended the referral and women who did not. Sonographers' exam findings were compared to referred women's recall. Results Among 700 referred women, 510 (71%) attended the referral. Among referred women, 97% received a referral card to present at the hospital, 91% were told where to go in the hospital, and 64% were told that the hospital was expecting them. The referred women who were told who to see at the hospital (88% vs 66%), where to go (94% vs 82%), or what should happen, were more likely to attend their referral (68% vs 56%). Barriers to attending referrals were cost, transportation, and distance. Barriers after reaching the hospital were substantial. These included not connecting with an appropriate provider, not knowing where to go, and being told to return later. These barriers at the hospital often led to an unsuccessful referral. Conclusions Our study found that ultrasound screening at ANC alone does not adequately address barriers to referrals. Better communication between the sonographer and the patient increases the likelihood of a completed referral. These types of communication include describing the ultrasound findings, including the reason for the referral, to the mother and staff; providing a referral card; describing where to go in the hospital; and explaining the procedures at the hospital. Thus, there are three levels of communication that need to be addressed to increase completion of appropriate referrals-communication between the sonographer and the woman, the sonographer and the clinic staff, and the sonographer and the hospital. Trial registration NCT01990625.